2023
DOI: 10.3390/antiox12020229
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Deficiency-Induced Oxidative Stress Causes Myocardial Injury in Calves by Activating Inflammation, Apoptosis, and Necroptosis

Abstract: Selenium (Se) is essential for human and animal health, but there have been few studies on the mechanisms of injury in dairy cows with Se deficiency. This study aimed to evaluate the effects of Se deficiency on myocardial injury in weaned calves. The Se-D group had significantly lower myocardial Se concentrations than the Se-C group. Histological analysis indicated that Se deficiency induced a large area of necrosis in the myocardium, accompanied by inflammatory changes. Se deficiency significantly decreased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…Se is an essential component as well as the active center of selenoprotein. The present study found that inadequate dietary Se led to a decrease in blood and lung Se levels in calves, and the effects of dietary Se on tissues were generally consistent with a previous study [ 20 ]. A decrease in Se is detrimental to the synthesis and activity of selenoproteins [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Se is an essential component as well as the active center of selenoprotein. The present study found that inadequate dietary Se led to a decrease in blood and lung Se levels in calves, and the effects of dietary Se on tissues were generally consistent with a previous study [ 20 ]. A decrease in Se is detrimental to the synthesis and activity of selenoproteins [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…A decrease in Se is detrimental to the synthesis and activity of selenoproteins [ 22 ]. Changes in selenoprotein mRNA expression in the lungs differed slightly from the results in the hearts of selenium-deficient calves [ 20 ]. The synthesis priority and distribution differences in the organs of selenoproteins caused differences in expression levels during Se deficiency [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Recommended Dietary Allowance (RDA) of Se for healthy individuals above 50 years is 55 μg; however, the recommendation may be higher depending on the region and patients’ characteristics [13]. Se deficiency has been strongly associated with thyroid nosology, particularly with Hashimoto thyroiditis [14,15 ▪ ] and with cardiovascular diseases [16] as Se regulates inflammation, oxidative stress, apoptosis, and necroptosis [17]. Variable anticancer activity has been shown by Se supplementation in thyroid cancer patients [18].…”
Section: Nutrients and The Thyroidmentioning
confidence: 99%